Kedudukan Harta Bersama yang Terletak di Luar Negeri (Singapura) dari Perkawinan Campuran yang Melakukan Perceraian di Pengadilan Negeri (Studi Putusan No. 552/Pdt.G/2013/PN.DPS) - Afridah Afridah; Yaswirman Yaswirman; Ferdi Ferdi (UNES Law Review, 2023)
A mixed marriage will bring legal consequences to the parties who do it, namely related to property in the marriage. The joint assets formed during the marriage are not only located in the territory of Indonesia, but also located abroad (Singapore). This study examines the position of joint assets in mixed marriages located outside the territory of Indonesia who filed for divorce and property claims in the District Court. The purpose of this article, which is based on the results of this research, aims to determine legal certainty regarding the status of joint property in mixed marriages located abroad (Singapore) based on Decision No. 552 / Pdt.G/2013/PN.Dps) by Judge. The research method used in this study is a normative legal research method with a source of law, namely statutory regulations. The research method used is a normative juridical approach. Research specifications use analytical descriptive and data sources use secondary data consisting of primary legal materials, secondary legal materials, and tertiary legal materials. Materials from the results of this study indicate that joint assets located abroad (Singapore) are subject to the Indonesian Judge's decision. In the eligibility conditions in the Strata Title rules that apply in Singapore, the holder of a Permanent Resident permit has the right to transfer or sell property located in that country.